The Application of Sentinel-2 Data for Automatic Forest Cover Changes Assessment - Białowieża Primeval Forest Case Study - Pelc-Mieczkowska, Renata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sentinel-2 mission, as a part of European Space Agency Earth Observation Program Copernicus, designed specifically for Earth surface observations provides images in 13 bands. That imaging is used to analyse many subject areas as Land monitoring, Emergency management, Security and Climate change.
Keywords: Białowieża Primeval; forest cover; remote sensing; radiometric indices; Sentinel-2; Puszcza Białowieska; lesistość; teledetekcja; wskaźniki radiometryczne